Navigating Digital Transformation Challenges: An In-depth Analysis of IT Governance in the Media Industry Using COBIT 2019 - Jonathan Sutanto; Melissa Indah Fianty; Eryanto Chandra; Jessica Jessica; Azzahra Shaffira; Yohanes Victor (G-Tech: Jurnal Teknologi Terapan, 2024)
This research was conducted with the main objective of evaluating and improving Information Technology (IT) Governance in an Indonesian media company facing significant challenges due to digital transformation. In the methodological approach, the study utilized the COBIT 2019 framework, involving planning, field implementation, reporting, and follow-up processes. The results of the capability level evaluation revealed a gap between actual achievements and desired targets, especially in the aspects of Managed Innovation (APO04) and Managed IT Changes (BAI06). The implications of these findings emphasize the need for improvements in activities related to managed innovation and IT change. The conclusion of this research underscores the urgency of effective IT governance in navigating the dynamics of digital transformation. It is hoped that these findings will serve as a guide for media companies and other organizations to formulate robust IT policies, enhance sustainable operations, and drive innovation in this digital era.